An investigation into the optimisation of a solar photocatalytic continuous flow disinfection system - Misstear, David (Trinity College (Dublin, Ireland). Department of Civil, Structural and Environmental Engineering, 2010)
Solar photocatalytic disinfection is thought to be a safe, effective, low-cost method of drinking water treatment and would be applicable, for example, to village-scale systems in developing countries. In this thesis, an investigation is carried out into factors affecting the photocatalytic disinfection of water.
Keywords: Civil, Structural and Environmental Engineering, Ph.D.; Ph.D. Trinity College Dublin.